Phenotypic Reprogramming of Striatal Neurons into Dopaminergic Neuron-like Cells in the Adult Mouse Brain - Niu, Wenze (Stem Cell Reports, 2018)
Neuronal subtype is largely fixed in the adult mammalian brain. Here, however, we unexpectedly reveal that adult mouse striatal neurons can be reprogrammed into dopaminergic neuron-like cells (iDALs). This in vivo phenotypic reprogramming can be promoted by a stem cell factor (SOX2), three dopaminergic neuron-enriched transcription regulators (NURR1, LMX1A, and FOXA2), and a chemical compound (valproic acid). Although the site of action of the reprogramming factors remains to be determined, immunohistochemistry and genetic lineage mappings confirm striatal neurons as the cell origin for iDALs. iDALs exhibit electrophysiological properties stereotypical to endogenous dopaminergic rather than striatal neurons. Together, these results indicate that neuronal phenotype can be reengineered even in the adult brain, implicating a therapeutic strategy for neurological diseases.